Acid and low temperature treatments on Salmonella Enteritidis inoculated in pork and its subsequent survival in simulated gastric fluid - Santos, Míriam Teresinha dos; Paes, Simone Albino; Vanetti, Maria Cristina Dantas; Silva, Simone Quintao (Ciência Rural, 2016)
The objective of this study was to evaluate the acid resistance of Salmonella enterica serovar Enteritidis (S. Enteritidis) in stored pork and in simulated gastric fluid (SGF). A culture of S. Enteritidis was subjected to acid treatment prior to inoculation into pork, stored under refrigeration at frozen temperatures and exposed to SGF. The S. Enteritidis CCS3 and ATCC 13076 strains previously subjected to acid treatment (at pH 4.0-5.0) were inoculated in pork and stored at 4[degrees]C and -18[degrees]C. Storage at 40C did not affect the populations of both S. Enteritidis strains. After 84 days at -18[degrees]C, the mean population of both CCS3 and ATCC strains were reduced by 0.8 and 1.5 log cycles, respectively. Prior acid treatment did not enhance the survival of both strains at low temperatures. After acid treatment and low temperature storage, S. Enteritidis ATCC 13076 lost culturability after being exposed to SGF for 10 minutes. In contrast, S. Enteritidis CCS3 was tolerant until three hours of SGF exposure. S. Enteritidis CCS3 submitted to pH 4.0 was more tolerant to SGF exposure than when submitted to pH 4.5, 5.0 and without acid treatment. Therefore, this study indicates that exposure to an acidic and cold environment during processing enhanced the ability of S. Enteritidis to survive in the gastric environment of the human stomach, possibly increasing the risk of a Salmonella infection after consumption of pork.

O objetivo deste estudo foi avaliar a resistencia ao acido de Salmonella enterica serovar Enteritidis (S. Enteritidis) previamente submetidas a tratamento acido e inoculadas em carne suina armazenada em temperaturas de refrigeracao e congelamento ao fluido gastrico simulado (FGS). As linhagens de S. Enteritidis CCS3 and ATCC 13076 previamente submetidas a tratamento acido variando de pH 4.0 a 5.0 foram inoculadas em carne de porco e armazenadas a 4 e -18[degrees]C. A estocagem por sete dias a 4[degrees]C nao afetou as populacoes das duas linhagens de S. Enteritidis. Apos 84 dias a -18[degrees]C, as reducoes medias das populacoes das linhagens foram de 0,8 e 1,5 ciclos logaritmicos, respectivamente. O tratamento acido previo nao aumentou a sobrevivencia das duas culturas sob baixas temperaturas. Apos tratamento acido e estocagem em temperaturas baixas, S. Enteritidis ATCC 13076 perdeu a culturabilidade apos 10 minutos de desafio ao FGS. Contrariamente, S. Enteritidis CCS3 mostrou-se tolerante a exposicao por tres horas ao FGS. S. Enteritidis CCS3 submetidas a tratamento acido previo em pH 4,0 mostraram-se mais tolerantes a exposicao por 180 minutos ao FGS que celulas submetidas aos tratamentos acidos em pH 4,5 e 5,0 e celulas sem tratamento. Portanto, este estudo indica que S. Enteritidis submetida a um ambiente acido e frio durante o processamento pode melhorar a sua capacidade de sobreviver a barreira gastrica em humanos, possivelmente, aumentando o risco de surto por Salmonella apos consumo de carne de porco.
Keywords: Acid resistance; SGF; Freezing survival; Storage survival; Cross-resistance; Resistência a ácido; FGS; Sobrevivência ao congelamento; Sobrevivência à estocagem; Resistência-cruzada